Artificial Bee Colonies Solution for Load Sharing in a Cloud RAN - Eric Michel, DEUSSOM DJOMADJI; NDJE BIHOLONG Evelyne Noelle; TONYE Emmanuel (European Journal of Applied Sciences, 2022)
The integration of the cloud in the access network architecture, through the Cloud RAN, allows to increase the network capacity thanks to the virtualization of the base station and the sharing of cloud resources. The great innovation of this concept is the BBU Pool present in the architecture. It is the pool that allows the term "centralized" to be used. The processing that is carried out there is critical for the operation of the entire network. Indeed, in a cloud based environment such as the C-RAN, it is important that the resources are used optimally. This is where load-balancing comes in, which is defined as a technique used to evenly distribute workloads across multiple servers or other computing resources to optimize network performance, reliability and capacity. This paper proposes a load balancing algorithm in the BBU pool of a C-RAN. It is based on the artificial bee colony metaheuristic (ABC algorithm) and on the Load Balanced Min-Min Algorithm (LBMM). All this is done to improve network performance by guaranteeing high availability of centralized and shared resources. Its effectiveness in terms of performance and execution time against Round Robin and MIN MIN algorithms is studied and the results are appreciable.